Źródło usprawiedliwienia w świetle "Homilii na List św. Pawła do Rzymian" Jana Chryzostoma - Drygier, Mariusz (Vox Patrum, 2020)
In The Homilies on the Epistle of St. Paul to Romans, John Chrysostom enunciates the traditional teaching of the Church about righteousness of a man. According to him, since the beginning of the salvation history, God has aimed to give people the free grace of righteousness, as with Abraham who was justified not because of the acts following from the Law of Moses, but because of his faith in the promises of God. For John the Golden-Mouthed the origin of the justifying grace lies in the Gospel, especially the passion, death and resurrection of Jesus Christ. By the intercession of the Redeemer the justice of God became accessible to a mortal. In order that the state of righteousness be real and effective for mankind, two individual acts are necessary: faith in God and baptism as a sign of unification with Christ.